Local ownership as international governmentality: Evidence from the EU mission in the Horn of Africa. Issue 1 (2nd January 2018) - Ejdus, Filip
ABSTRACT: While some Foucault-inspired studies construe local ownership in international interventions as a form of liberal governmentality that aims to govern through freedom, others lambast it as an illiberal governmentality that is likely to be resisted because it undermines local autonomy. However, we still do not know what is the rationality behind local ownership, how it is being operationalized, and why a principle that aims to govern through freedom ends up curtailing it. I argue that local ownership, echoing the colonial principle of indirect rule, is driven by the rationality of advanced democracies on how best to govern global insecurities at a distance. Consequently, ownership is operationalized as responsibilization for externally designed objectives. This often gives rise to local resistance which undermines international efforts to achieve ownership. I illustrate my arguments with evidence from the EU Mission on Regional Maritime Capacity Building in the Horn of Africa (EUCAP Nestor).